User Cost and Irish House Prices - DUFFY, DAVID (My University, 2011)
A measure commonly used to assess house prices is the house price?to? rent ratio. This ratio captures the costs of alternative forms of accommodation, namely buying or renting. In the long run these two costs should move together. If house prices rise compared to rents, more people may choose to rent rather than buy. This drives rents up and house prices down. In other words, if the alternative costs of accommodation are not moving together then people would switch between buying and renting. This would continue until the alternative costs again begin to move in line with each other.
PUBLISHED
Keywords: Economics; Ireland; House prices